Literatura e memória em Pedro Nava: a ficcionalização da experiência por uma poética do passado. - Costa, José Carlos da (2009)
This work deals the memoirist work of Pedro Nava in the contemporary fiction context, and reflecting on the borders and crossings among memory, history and fiction. The foundation of the work is in the status of representation, its conformation in the literary text relatively to the perspective of the memoirist novel and the more frequent marks in this kind of narrative. Careful memoirist, the author build his report based on not only in his memories, but also in saved documents and researches about the facts of the time he is reporting, pictures of persons and events he took part. This set of supporting elements grounds the truth of his report and fill the blanks of the memory. In this point Galo-das-trevas: as doze velas imperfeitas (Memories 5), when talking about the beginning of his professional career, Nava resize his early memoirist project and the narrative becomes conducted by a omniscient narrator that report in third person. This fact changes the narrative fulcrum to the life of his alter ego: José Egon de Barros Cunha, taking a new direction and rearticulates the autobiographical pact , transforming it in novel pact . The selection of this work among the seven volumes of Nava s memory is justified by the meaningful change of the form of the reporting introduced from the second part of the book.